Renovation of existing steel railway bridges: Field test and numerical simulation. Issue 6 (April 2018) - Lin, Weiwei; Taniguchi, Nozomu; Yoda, Teruhiko; Hansaka, Masanori; Satake, Shinya; Sugino, Yusuke
Renovation of the aged steel railway structures is of vital importance due to their long service life after completion. A strengthening method for aged steel railway bridges by using rubber-latex mortar, glass fiber–reinforced polymer plates, lightweight rapid hardening concrete, and reinforcing bars was introduced in this article. To confirm the real effect of the present strengthening method, field tests were performed on two aged steel railway bridges that have been in service for 87 and 61 years, respectively. Stress variations on the mid-span section of the railway bridge due to the running trains were measured in the field test, and the stress reduction effects as well as the load redistribution effects of the present strengthening method were also confirmed. Three-dimensional finite-element models were built, and the numerical results were in good agreement with the field test results. Besides, structural vibration and noise levels of both strengthened and un-strengthened railway bridges were measured, and the noise reduction effect of the present method was confirmed in the field tests. In addition, further nonlinear analyses were performed, and the applied load–displacement relationships as well as the load–normal longitudinal strain curves of the aged structural steel, the glass fiber–reinforced polymer plates and the rapid hardening concrete, were given. Both experimental and numerical results indicate that the present renovation method can greatly enhance the stiffness and reduce the stress levels of steel members, resulting in the extension of the residual service life of the aged steel railway bridges.